Smoking: ban all forms of tobacco - Nik Mohamed, Mohamad Haniki (New Straits Times Press (NSTP), 2011)
REFER to reports calling for a ban on shisha smoking and wonder if we are missing the bigger picture. Tobacco use is the leading preventable cause of death. According to the World Health Organisation, more than five million people will die from tobacco-related heart attacks, strokes, cancer, lung ailments or other diseases this year. That does not include the more than 600,000 people -- more than a quarter of them children -- who will die from exposure to second-hand smoke. The annual death toll from the global epidemic of tobacco use could rise to eight million by 2030. Having killed 100 million people in the 20th century, tobacco use could kill one billion in the 21st century.